Asian drama. An inquiry into the poverty of nations. [In collab. with W.J. Barber, A. Majava, A. Myrdal a.o. With forew. by A. Heckscher] (Pantheon, A division of Random House, 1968)
With graphs, indices, maps and tabs. A twentieth century fund study.